The Visual Arts Education Crisis in Malaysia: Placement of Students into the Arts Curricular Stream at the Upper Secondary Level in Malaysian Secondary Schools - Ahmad Suffian Asmawi Ponijan; Mohamad Faizuan Mat; Sarah Naemah Aman Leong (Journal of Visual Art and Design, 2019)
In Malaysia, the curricular subject of visual art, especially at secondary school level, pays little attention to the aspect of artistic knowledge development. Students are assigned to the arts stream based on their Level Three assessment results, which ultimately causes problems in the visual art learning process in the classroom. On the other hand, formal art education is absent among students in the science stream and visual art is perceived to be only for underperforming students, when in fact visual art can be a valuable subject for all students. This study used a qualitative triangulation method to assess the similarities between data from face-to-face interviews, observations and literature study. Visual arts education is duly needed at the upper secondary level of education in Malaysia to cultivate future generations with creative and critical minds. However, does the art education offered in the arts stream actually benefit the students who are assigned to this curricular stream based on the existing student placement system? This study aimed to investigate problems and issues in Malaysian visual arts education based on the system of student placement into curricular streams.